Systematic review of different surgical contraception techniques in queens - Toledo Valdez, Cielo; Rivera Barreno, Ramon; Rodríguez-Alarcón, Carlos Arturo; García Herrera, Ricardo (2021)
In the veterinary clinic, contraceptive surgery is the most commonly performed surgery in female cats. However, it is not established which surgical technique is the most appropriate. In order to reduce postoperative pain, recovery time, surgery time and technical ease for the surgeon, different surgical techniques and variations of these techniques have been described. This has created the dilemma of performing ovariohysterectomy versus oophorectomy; type of approach: midline, lateral or laparoscopic; and method of ovarian pedicle ligation: harmonic scalpel, plastic and titanium clips, bipolar electrosurgical unit, pedicle knot and traditional ligation. With this in mind, with the objective of establishing which is the most adequate contraceptive surgery in female cats and supported by evidence-based medicine, a systematic review was carried out. Using Google Scholar, Web of Science, PubMed and SciELO search engines, with the following variables to be evaluated: pain, time and technical difficulty. It was found that there is little evidence to establish the superiority of any surgical technique over another and that the choice of surgical technique should be made based on the patient, the surgeon's skills and the availability of materials